2018
DOI: 10.1590/s1980-220x2016042703330
|View full text |Cite
|
Sign up to set email alerts
|

Emoção expressa de familiares e recaídas psiquiátricas de pacientes com diagnóstico de esquizofrenia

Abstract: Objective: Assess the relationship between psychiatric relapses of patients with a diagnosis of schizophrenia, the levels of expressed emotion among their relatives and related factors. Method: Prospective study carried out at a mental health outpatient clinic and two Psychosocial Care Centers, with patients and relatives responding to the Family Questionnaire -Brazilian Portuguese Version, a form containing socio-demographic and clinical variables and a structured script to assess relapses. A logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
3
1
3
Order By: Relevance
“…No Brazilian studies were found that investigated caregivers' EE in moments of patient psychiatric crisis. However, Zanetti et al (2018b), in a recent study conducted in Brazil with 89 relatives of people with schizophrenia found a high EE of 49% and 52% in the CC and EOD components, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…No Brazilian studies were found that investigated caregivers' EE in moments of patient psychiatric crisis. However, Zanetti et al (2018b), in a recent study conducted in Brazil with 89 relatives of people with schizophrenia found a high EE of 49% and 52% in the CC and EOD components, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…EE is a relevant measure because several studies showed that people with mental disorders from families with high EE have a worse prognosis of the disease and more episodes of psychiatric acute than those from families with low EE (AHMAD et al, 2017;ZANETTI et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Um agravante são os comentários críticos, que estão relacionados à avaliação negativa da conduta do paciente; a hostilidade, a avaliação negativa do paciente como pessoa; e o super envolvimento emocional, que se refere aos sentimentos ou atitudes, à desesperança, ao auto sacrifício e à superproteção do paciente por parte dos familiares (Zanetti, 2019).…”
Section: Família E Sobrecarga Dos Cuidadoresunclassified
“…8 Atribui-se o surgimento da metodologia de EE ao contexto de desenvolvimento da Psiquiatria Social e Comunitária, nos anos 1950/1960, principalmente aos desdobramentos do trabalho do psiquiatra George W. Brown. É apontada como uma metodologia eficaz para reconhecer o que se chama de atmosfera emocional que circunda pacientes ditos esquizofrênicos (WEARDEN et al, 2000;ZANETTI et al, 2018;SANTOS et al, 2005). Amaresha e Venkatasubramanian (2012) informam que ela emergiu do próprio processo de desinstitucionalização que se seguiu ao surgimento da clorpromazina, processo que foi, apesar do "sucesso" da medicação, sucedido pela readmissão de muitos sujeitos a contextos institucionais devido a recaídas e reincidência de sintomas.…”
Section: Notasunclassified